Association between catechol‐O‐methyl transferase gene polymorphisms and fibromyalgia in a Korean population: A case–control study. (5th February 2016) - Park, D.J.; Kim, S.H.; Nah, S.S.; Lee, J.H.; Kim, S.K.; Lee, Y.A.; Hong, S.J.; Kim, H.S.; Lee, H.S.; Kim, H.A.; Joung, C.I.; Kim, S.H.; et al.
Abstract: Background: Although polymorphisms of the catechol‐O‐methyl transferase (COMT) gene have been implicated in altered pain sensitivity, results concerning the association between COMT gene polymorphisms and fibromyalgia (FM) are equivocal. We assessed the associations between COMT single‐nucleotide polymorphisms (SNP) and FM risk and symptom severity. Methods: In total, 409 FM patients and 423 controls were enrolled. Alleles and genotypes at five positions [rs6269 (A>G), rs4633 (C>T), rs4818 (C>G), rs4680 (C>G) and rs165599 (A>G)] in the COMT gene were genotyped from peripheral blood DNA. Results: Alleles and genotypes of the rs4818 COMT gene polymorphism were significantly associated with increased susceptibility to FM. The rs4818 GG genotype was more strongly associated with FM compared to the CC genotype (OR = 1.680, 95% CI: 1.057, 2.672, p  =   0.027). Although allele and genotype frequencies did not differ among groups, the rs4633 CT genotype was not associated with the presence of FM following adjustment for age and sex (OR = 0.745; 95% CI: 0.558, 0.995; p  =   0.046). However, no association was observed between clinical measures and individual COMT SNPs. In haplotype analysis, there was a significant association between ACG haplotype and FM susceptibility sex (OR = 2.960, 95% CI: 1.447, 6.056, p  =   0.003) and the number of tender points ( p  =   0.046). Conclusions: This large‐scale study suggests that polymorphisms of the COMT gene may be associated with FM risk and pain sensitivity in Korean FM patients. However, our results differed to those of previous studies, suggesting ethnic variation in COMT gene polymorphisms in FM. What does this study add: By contrast to Caucasian and Latin‐American populations, the COMT gene polymorphisms are associated with FM risk and pain sensitivity in Korean FM patients, suggesting ethnic variation in COMT gene polymorphisms.